Perceptions of Online Lending Risks: A Netnographic Analysis of Indonesian YouTube Videos - Alim, Ahmad Syahirul (Ekonomi Islam Indonesia, 2025)
This study examines public discourse concerning online loans in Indonesia through a Netnography analysis of YouTube user comments on videos about this topic. Data was gathered from 19 videos, which collectively garnered 51,279 comments, and were analyzed using NVivo software to perform a qualitative analysis. The methodology went beyond simple data collection, employing sentiment and thematic analysis to identify user perceptions. The findings indicate a notable prevalence of negative sentiments toward online loans, particularly illegal ones, frequently linked to detrimental practices such as aggressive debt collection, exorbitant interest rates, and the misuse of personal data. Users on YouTube raised various concerns regarding online loans, including the risk of default, unethical debt collection methods, and data privacy violations. Despite being aware of these risks, some individuals continue to engage with online loan services due to urgent financial needs and the convenience they offer. Discussions also emerged about the obligation to repay debts incurred from illegal online loans, highlighting a gap in public comprehension of Islamic economic principles and emphasizing the need for sharia-compliant regulations and appropriate legal frameworks.This study recommends enhancing regulations, oversight, and law enforcement related to online loans and promoting sharia financial literacy within the community. Additionally, the development of Sharia-compliant peer-to-peer lending are anticipated to provide fairer and more responsible digital financial services.